Maternal ambient heat exposure during early pregnancy in summer and spring and congenital heart defects – A large US population-based, case-control study. (September 2018) - Lin, Shao; Lin, Ziqiang; Ou, Yanqiu; Soim, Aida; Shrestha, Srishti; Lu, Yi; Sheridan, Scott; Luben, Thomas J.; Fitzgerald, Edward; Bell, Erin; Shaw, Gary M.; Reefhuis, Jennita; et al.
Abstract: Background/objective: Few studies have assessed the effect of ambient heat during the fetal development period on congenital heart defects (CHDs), especially in transitional seasons. We examined and compared the associations between extreme heat and CHD phenotypes in summer and spring, assessed their geographical differences, and compared different heat indicators. Methods: We identified 5848 CHD cases and 5742 controls (without major structural defects) from the National Birth Defects Prevention Study, a US multicenter, population-based case-control study. Extreme heat events (EHEs) were defined by using the 95th (EHE95) or 90th (EHE90) percentile of daily maximum temperature and its frequency and duration during postconceptional weeks 3–8. We used a two-stage Bayesian hierarchical model to examine both regional and study-wide associations. Exposure odds ratios (ORs) were calculated using multivariate logistic regression analyses, while controlling for potential confounding factors. Results: Overall, we observed no significant relationships between maternal EHE exposure and CHDs in most regions during summer. However, we found that 3–11 days of EHE90 during summer and spring was significantly associated with ventricular septal defects (VSDs) study-wide (ORs ranged: 2.17–3.24). EHE95 in spring was significantly associated with conotruncal defects and VSDs in the South (ORs: 1.23–1.78). Most EHE indicators in spring were significantly associated with increased septal defects (both VSDs and atrial septal defects (ASDs)) in the Northeast. Conclusion: While generally null results were found, long duration of unseasonable heat was associated with the increased risks for VSDs and ASDs, mainly in South and Northeast of the US. Further research to confirm our findings is needed. Highlights: Exposure to extreme heat in summer was not consistently related to heart defects. Conotruncal and septal defects were associated with long duration of heat in spring. The adverse effects of unseasonable heat were found in the South and Northeast US. Cumulative number of heat days was the most sensitive indicator. It is critical to issue early warnings against heat's impact in transitional season.